A comparative study between Malaysia law and law in England: protection of seahorse / Nur Bainy Mohd Raimay ... [et al.] - Mohd Raimay, Nur Bainy; Bukhari, Nor Syamimi; Zainal Alam, Nur Azwani; Shahruddin, Nurul Atiqah; Roslin, Nur Fatin Nadia (2010)
Seahorses suffer threat of extinction because of overharvested by human because seahorses are largely use for the Traditional Chinese Mediexcine. The impact of the seahorse's extinction could actually affect the balance of marine food web of the aquatic lives. This research contains differences between Malaysian Law and United Kingdom law in dealing with the protection of seahorses which included the discussion on the comparison on Fisheries Act 1985 in Malaysia and Wildlife and Countryside Act 1981 in United Kingdom. The comparison reflects that local law does not provide adequate protection to seahorses in terms of protection and enforcement since Malaysia is a party to CITES (Convention on International Trade in Endangered Species of Wild Fauna and Flora) and is bound to do so. Library based research are conducted and these constructive information are recorded and conclusions are made. Therefore, there is a need for the amendment for adequate protections of seahorses in terms of sufficiency of the punishment, protection and enforcement of the local law.